Application of the Skilbeck Model Curriculum Development in Elementary Schools in School Quality Assurance Efforts - Noptario Noptario; Alia Latifah; Happy Fitria; Fitria Nurliana Zulfa (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The curriculum is a school design as a guideline for implementing learning activities to achieve educational goals. Curriculum development is an effort made so that the curriculum used is relevant to use according to the conditions that exist in schools. Many schools only imitate the curriculum from other educational units and do not develop a curriculum using the curriculum development model. The purpose of this study is to reveal the application of the Skillbeck model of curriculum development in an effort to guarantee school quality which is expected to be useful for schools as a reference in efforts to develop curriculum in their schools. This study uses a qualitative research approach. While the data collection techniques used in this study were obtained through interviews. Interviews were conducted with 3 informants consisting of the school principal, vice curricula and class teacher. Data analysis techniques are carried out by condensing data, presenting data and drawing conclusions or verification. The Skilbeck curriculum development model is a curriculum development design that has the advantage of being structured in stages and able to answer existing problems with organized and clear stages. This can be seen from the systematic stages and being able to represent the goals of curriculum development. The difference between the Skillbeck curriculum development model and other curriculum development models is that the teacher has the right to determine the school curriculum so that it is in accordance with the goals to be achieved because this curriculum is dynamic. The skilbeck curriculum development model is carried out by carrying out five stages, namely situation analysis, formulating objectives, formulating programs, implementation, and finally monitoring and evaluation.